Pyloric atresia: A rare cause of neonatal gastrointestinal obstruction - Othmane alaoui; Abdelhalim Mahmoudi; Khalid Khattala; Youssef Bouabdallah (Elsevier, 2023)
Pyloric atresia (PA) is a rare malformation that constitutes less than 1% of all intestinal atresias and its incidence is approximately 1 in 100,000. Also, it's a very rare cause of neonatal bowel obstruction. Neonates usually present soon after birth with copious non-bilious vomiting. The treatment is surgical. Typically, it is an isolated malformation, with a good prognosis, but 20-40% of cases present epidermolysis bullosa which are considered more serious. We report the case of three-day-old girl successfully treated for isolated form of pyloric atresia occurring in the context of neonatal gastrointestinal obstruction.